2010
DOI: 10.1051/0004-6361/200913518
|View full text |Cite
|
Sign up to set email alerts
|

VLT observations of NGC 1097's “dog-leg” tidal stream

Abstract: Aims. We investigate the structure and stellar population of two large stellar condensations (knots A & B) along one of the faint optical "jet-like" tidal streams associated with the spiral NGC 1097, with the goal of establishing their physical association with the galaxy and their origin. Methods. We use the VLT/FORS2 to get deep V-band imaging and low-resolution optical spectra of two knots along NGC 1097's northeast "dog-leg" tidal stream. With this data, we explore their morphology and stellar populations.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 66 publications
(46 reference statements)
3
37
0
Order By: Relevance
“…Indeed, other extragalactic post‐merger cases of aligned dSph satellites with tidal arms have emerged (Malphrus et al 1997; Bournaud et al 2007; Galianni et al 2010; Duc et al 2011), strengthening the notion that dSph and dwarf elliptical (dE) satellites are old TDGs (Okazaki & Taniguchi 2000). The implications of this for cosmological theory and fundamental physics are discussed in Kroupa et al (2010) and Kroupa (2012).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, other extragalactic post‐merger cases of aligned dSph satellites with tidal arms have emerged (Malphrus et al 1997; Bournaud et al 2007; Galianni et al 2010; Duc et al 2011), strengthening the notion that dSph and dwarf elliptical (dE) satellites are old TDGs (Okazaki & Taniguchi 2000). The implications of this for cosmological theory and fundamental physics are discussed in Kroupa et al (2010) and Kroupa (2012).…”
Section: Discussionmentioning
confidence: 93%
“…TDGs are found to form both in simulated (Bournaud & Duc 2006;Wetzstein, Naab & Burkert 2007;Bournaud, Duc & Emsellem 2008) and observed (Mirabel, Dottori & Lutz 1992;Hunsberger, Charlton & Zaritsky 1996;Weilbacher, Duc & Fritze-v. Alvensleben 2003) galaxy collisions. They seem to be long-lived objects (Kroupa 1997;Recchi et al 2007;Galianni et al 2010;Duc et al 2011) and share the same properties as dwarf elliptical (dE) galaxies (Dabringhausen et al, in preparation). This makes them a fundamental addition, if not even an alternative, to cosmologically formed dwarf galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…Their age estimate of these dwarf galaxies (at least 2 Gyr, but maybe up to 5 Gyr) demonstrates that TDGs are long‐lived objects which contribute to the population of satellite galaxies. Galianni et al (2010) discuss that the satellite galaxies of NGC 1097, embedded in a tidal stream, might be old TDGs. The stability of TDGs has also been investigated numerically.…”
Section: Discussionmentioning
confidence: 94%
“…This spatial alignment can be conserved over time. Galianni et al (2010) discuss that the satellite galaxies of NGC 1097, embedded in a tidal stream, might be old TDGs. Recently, Duc et al (2011) found three old TDG candidates, aligned along a tidal tail around the galaxy NGC 5557.…”
Section: Do Tdgs Align and Orbit In A Disc?mentioning
confidence: 94%
“…In the local universe there are a number of known host galaxies with stream-TDG satellite alignments: (1) The NGC 1097 'dog leg' stellar stream with two typical dSph satellite galaxies (Galianni et al 2010). (2) The about 300 kpc long tidal stream with at least three dSph satellite galaxies in the 1-2 Gyr old post-interaction NGC 5557 (Duc et al 2011).…”
Section: Other Extragalactic Satellite-stream Alignmentsmentioning
confidence: 99%